Pemanfaatan Sampah Organik Sebagai Pupuk Cair Berbasis Effective Microorganism 4 (Em4) untuk Pertanian (Jurnal Bina Desa, 2022)
Waste is a problem in its own community. Because of this, youth groups who care about the environment, "Utomo Resik" has so much attention about waste . One of the efforts has made by processing organic waste from agricultural residues into liquid fertilizer based on effective microorganism 4 (EM4). Starting from the KKN-PPM UNNES alt. IIA 2019 team held a training program in collaboration with UPT Bangvasi UNNES. From the training, the community especially members of the "Utomo Resik" began to change their behavior towards the environment and waste . Waste is usually just thrown away, is now sorted to be processed into liquid fertilizer. Leaves or rotten fruit that are usually only left in the fields are now collected to be processed into fertilizer. The presence of liquid fertilizer indirectly also helped the economy of citizens because it can reduced the cost of agricultural production. In addition, some residents, especially members of the "Utomo Resik" have taken the initiative to sell liquid fertilizer has made by them even though it is only marketed around the village. In the future, the liquid fertilizer are expected to be produced on an industrial scale.